Metode Servqual Dalam Analisa Kepuasan Pengguna Aplikasi Jakone Mobile Merchant - Prima, Harry; Ramanda, Kresna; Rusman, Arief; Sukmana, Sulaeman Hadi; Sikumbang, Erma Delima; Azizah, Qudsiah Nur (LPPM STIKOM Tunas Bangsa, 2024)
Jakone Mobile Merchant is a financial service application that allows to make transactions for daily needs at merchants that collaborate with Bank DKI, such as transaction information at merchants and electronic money transfers to Bank DKI savings accounts. One of the keys to success is providing excellent service to customers when using the Jakone Mobile Merchant application. In order to understand the level of satisfaction of application users. This measurement uses the Servqual method with five service quality dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Emphaty. This measurement makes it possible to provide recommendations on the level of user satisfaction. Results based on measuring five dimensions of service quality show that the two dimensions that influence service quality, namely the empathy dimension, have a result of -0.82. This means that this aspect of service needs to receive attention and become a priority for evaluation and assessment. Further improvement of service quality should be carried out by PT Bank DKI as the owner of the Jakone merchant mobile application